Предмет: Алгебра,
автор: Оуэна
6*(1,2x-0,5)-1,3x=5,9x-3
Ответы
Автор ответа:
0
7,2x-1,3x-5,9x=-3+3 => x=0
Автор ответа:
0
6 * (1,2х - 0,5) - 1,3х = 5,9х - 3
7,2х - 3 - 1,3х = 5,9х - 3
5,9х - 5,9х = - 3 + 3
0 = 0 - уравнение не имеет решений
7,2х - 3 - 1,3х = 5,9х - 3
5,9х - 5,9х = - 3 + 3
0 = 0 - уравнение не имеет решений
Похожие вопросы
Предмет: Химия,
автор: hellgame
Предмет: Геометрия,
автор: anastasiaivanova2580
Предмет: Алгебра,
автор: viktoriagorbac8
Предмет: Математика,
автор: mah2765
Предмет: Экономика,
автор: CasEmanuel